Comparison of the effects of parecoxib and diclofenac in preemptive analgesia: A prospective, randomized, assessor-blind, single-dose, parallel-group study in patients undergoing elective general surgery - Bajaj, Parina (Elsevier, 2004)
BACKGROUND: Preoperative administration of analgesics may prevent or reducehyperalgesia, inhibit inflammation, and reduce pain by reducing the synthesis of prostaglandins in response to tissue damage caused by surgery. Nonsteroidal anti-inflammatory drugs (NSAIDs) are a potent, widely used class of analgesic agents; however, they may not be as effective as selective cyclooxygenase (COX)-2 inhibitors. OBJECTIVE: The aim of this study was to compare the efficacy and tolerabilityof the COX-2 inhibitor parecoxib sodium and the NSAID diclofenac sodium as preemptive analgesics in patients undergoing elective general surgery. METHODS: This was a prospective, randomized, assessor-blind, single-dose,parallel-group, comparative trial. Patients aged 18 to 65 years undergoing elective general surgery were enrolled. A single IM injection of parecoxib 40 mg or diclofenac 75 mg was administered 30 to 45 minutes before the induction of anesthesia. Surgery was performed as per standard protocol. The primary measures of efficacy were pain intensity score (measured on a visual analog scale [VAS]), pain relief score, duration of analgesia, and platelet aggregation response to adenosine diphosphate. Tolerability assessment included monitoring of treatment-emergent adverse events (AEs), physical examination, laboratory analysis, electrocardiography, and chest radiography. RESULTS: Eighty patients (56 men, 24 women; mean [SD] age, 45.96 [12.83] years) were enrolled in the study (40 patients per treatment group). All patients completed the trial. No pain was reported by any patient in the parecoxib group up to 12 hours; in the diclofenac group, no pain was reported up to 6 hours. At 12 hours, the mean (SD) VAS score was 2.33 (1.39) (moderate pain) in the diclofenac group and 0 (no pain) in the parecoxib group (P < 0.05). At 12 hours, total pain relief was reported by all 40 patients (100.0%) in the parecoxib group but by none (0.0%) in the diclofenac group, and 2 patients in the diclofenac group (5.0%) reported good pain relief (between-group difference for total + good pain relief, P < 0.05). Mean (SD) duration of analgesia was significantly longer in the parecoxib group than in the diclofenac group (19.48 [5.61] hours vs 8.32 [4.11 ] hours; P < 0.05). Platelet aggregation was significantly inhibited in the diclofenac group (change from baseline, 64.0%) but not in the parecoxib group (change from baseline, 12.0%) (P < 0.05). Both regimens were well tolerated, and no AEs were reported. CONCLUSIONS: In this study of patients undergoing elective general surgery,patients treated with the COX-2 specific inhibitor parecoxib experienced no pain at 12 hours, and the treatment was well tolerated. The results of this study suggest that good postoperative analgesia and minimal interference with platelet function may make parecoxib an alternative to the nonselective NSAID diclofenac in providing preemptive analgesia in patients undergoing general surgery.